Application Status and Practical Analysis of Surrogate Endpoints in Clinical Trial Design for Orphan Drugs - Wang, Jieni (International Journal of Public Health and Medical Research, 2026)
Rare diseases are characterized by high heterogeneity, small patient populations and wide geographic dispersion. Clinical trials of orphan drugs generally face problems such as recruitment difficulties, long follow-up, and difficulty in evaluating traditional endpoints. Surrogate endpoints can indirectly predict clinical benefits and have become an important research tool for the design of clinical trials for rare disease drugs. This article refers to the accelerated approval rules of the US FDA, the conditional marketing authorization system of the EU EMA, and the relevant guidelines for clinical research and development of rare disease drugs in China. It systematically sorts out the regulatory norms and application system of surrogate endpoints, analyzes their implementation points, practical shortcomings, and potential safety risks in clinical trial design. Research has found that surrogate endpoints can effectively break through the experimental bottleneck of orphan drug development, but there are still many problems in indicator validation standards, practical application, and risk management. Based on the current situation of domestic research and development, this paper proposes targeted optimization strategies to provide practical references for the design of orphan drug trials, regulatory review, and clinical research in China. These strategies can not only accelerate the market entry of orphan drugs, but also keep clinical medication safety as a top priority.